Pengaruh Kecerdasan Emosional Terhadap Kinerja Anggota di Skadron Udara 1 - B31112143, Bayu Krisdani Budi (Jurnal Manajemen Update, 2017)
In the development of human resources management were modern, then it is the duty of management to study and develop the efforts of human beings can be integrated effectively into the organization dipimpinya. Similarly ditutut management to constantly develop new ways to attract and retain members of the unit and institution that can still flourish. One way is to practice emotional intelligence members to improve the performance of its performance with the aim of achieving the desired goals. In this case the man is the least resources play an important role in the survival of the organization. Therefore, emotional intelligence which is owned by the members will determine the degree of success of an organization in improving the performance of its members. This study entitled Effect of Emotional Intelligence in the Member Performance Against Air Squadron 1. The purpose of this study was to determine the factors of emotional intelligence and the performance of members in the Air Squadron 1 Supadio air base. The method used in this research is survey method with all members of the population in Air Squadron 1, amounting to as many as 84 people. Research variables used for emotional intelligence factors include self-awareness, self-regulation, motivation, empathy and social skills. Research variables used for the performance factors include the quantity of work, quality of work, use of time, attendance and cooperation. Based on the analysis of the study showed that the level of emotional intelligence includes self-awareness, self-regulation, motivation, empathy and social skills. is high. This is because the members feel that these factors may spur them to work better. This means for the future of emotional intelligence can be maintained optimally. While the results of the analysis to include the performance level of the quantity of work, quality of work, use of time, attendance and cooperation. is high. This is because the members were able to respond to every job they do. So in the end created a feeling to do their best to force Air Squadron 1.